Features of Improving the Law Enforcement Function of the State (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
The article describes the features of improving the law enforcement function of the state, proposals for improving the law enforcement function of the Republic of Uzbekistan, the opinions of scientists, and practical examples of research results.